Effect of maternal periodontitis on GLUT4 and inflammatory pathway in adult offspring - Mattera, Maria Sara de Lima Coutinho [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Lopes, Flávia Lombardi [UNESP]; Tsosura, Thaís Verônica Saori [UNESP]; Peres, Maria Angelica; Brito, Victor Gustavo Balera [UNESP]; de Oliveira, Sandra Helena Penha [UNESP]; Pereira, Renato Felipe [UNESP]; Marani, Fernando [UNESP]; Dos Santos, Rodrigo Martins [UNESP]; Belardi, Bianca Elvira [UNESP]; Tessarin, Gestter Willian Lattari [UNESP]; et al. (Wiley, 2019)
BACKGROUND: Maternal periodontal disease leads to low birth weight (LBW), insulin resistance (IR), increased TNF-α levels, and alterations in insulin signaling in adult offspring. TNF-α has been associated with the stimulation of IKKβ/NF-κB, resulting in the decreased expression of GLUT4. Another mechanism that may be involved in decreasing GLUT4 expression is DNA methylation. This study aimed to evaluate in the adult offspring of rats with periodontal disease: IR, inflammatory pathways, DNA methylation, and expression of GLUT4. METHODS: Female Wistar rats were distributed into control and experimental periodontal disease groups. Seven days after induction of periodontal disease, both groups were mated with healthy male rats. After weaning, male offspring were distributed into control offspring (CN-o) and periodontal disease offspring (PED-o) groups. Body weights were measured from 0-75 days of age. At day 75, the following were measured in the offspring: IR (HOMA-IR index); TNF-α and NF-κBp65 content in the gastrocnemius muscle (GM) by western blotting; IKKα/β, JNK, ERK 1/2, NF-κBp65, and NF-κBp50 phosphorylation status in the GM by western blotting; DNA methylation by restriction digest and real-time PCR(qAMP); and expression of GLUT4 mRNA in the GM by real-time PCR. RESULTS: LBW, IR, increases in TNF-α, IKKα/β, ERK 1/2, NF-κBp65, and NF-κBp50 decreased expression of GLUT4 mRNA were observed in the PED-o rats. No differences were identified in JNK phosphorylation status and DNA methylation in the evaluated regions of the GLUT4-encoding gene Slc2a4. CONCLUSION: Maternal periodontal disease causes LBW, IR, activation of inflammatory pathways, and decreased GLUT4 expression in the GM of adult offspring.
Keywords: diabetes mellitus; DNA methylation; glucose transporter type 4; low birth weight; periodontal diseases; tumor necrosis factor-alpha